2015
DOI: 10.1186/s12889-014-1338-1
|View full text |Cite
|
Sign up to set email alerts
|

Weekday and weekend patterns of objectively measured sitting, standing, and stepping in a sample of office-based workers: the active buildings study

Abstract: BackgroundThere is a growing body of research into the total amount and patterns of sitting, standing and stepping in office-based workers and few studies using objectively measured sitting and standing. Understanding these patterns may identify daily times opportune for interventions to displace sitting with activity.MethodsA sample of office-based workers (n = 164) residing in England were fitted with thigh-worn ActivPal accelerometers and devices were worn 24 hours a day for five consecutive days, always in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
97
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(116 citation statements)
references
References 32 publications
14
97
0
5
Order By: Relevance
“…Similar to previous research the sedentary behavior remained rather stable between weekday and weekend days [56,57,58]. In addition, the values for time spent sitting in the current study fell within values found in previous research assessing similar relations in young adults [35,59], and physical activity engagement group distribution in the current study was congruent to the distribution found in the 2011 BRFSS data [8,18].…”
Section: Discussionsupporting
confidence: 90%
“…Similar to previous research the sedentary behavior remained rather stable between weekday and weekend days [56,57,58]. In addition, the values for time spent sitting in the current study fell within values found in previous research assessing similar relations in young adults [35,59], and physical activity engagement group distribution in the current study was congruent to the distribution found in the 2011 BRFSS data [8,18].…”
Section: Discussionsupporting
confidence: 90%
“…The STS is performed many times in daily life. According to previous studies, the number of STS movements is about 52 ± 13 times/day (Smith et al 2015), 60 ± 22 times/day (min-max: 10-124 times) (Dall and Kerr 2010) and 6 ± 3 times/h during waking time for 16 h (Alkhajah et al 2012) in office workers, and 54 ± 15 and 71 ± 25 in older adults (Fitzsimons et al 2013;Grant et al 2011). These previous studies suggest that some individuals perform only 10-15 STS movements per day, whereas others perform over 100 such movements.…”
Section: Discussionmentioning
confidence: 93%
“…However, defining physical activity as being strictly complementary to sedentary time (ie, equivalent to "non-sedentary time") deviates from some previous studies (54,55). This reflects an inconsistency in the literature regarding how to define physical activity.…”
Section: Gupta Et Almentioning
confidence: 88%